Anion-exchange-mediated internal electric field for boosting photogenerated carrier separation and utilization - Tong Han (Nature Portfolio, 2021)
Research on the bulk internal electric field (IEF) regulation is significant for designing high-efficiency photocatalysts. Here, the authors report distinctive bismuth oxyhydroxide nanorods photocatalyst and increase the bulk IEF intensity by halogen ions exchange.